Clinical applications of pharmacogenomics to adverse drug reactions. Issue 2 (March 2008) - Issa, Amalia M
The problem of adverse drug reactions is a well-documented global public health problem. Recent withdrawals of several widely used prescription medications in the USA and other countries have raised concerns among patients, clinicians, scientists and policy makers. The increasing interest and concern regarding withdrawal of previously approved prescription medications and drug safety has prompted renewed research efforts aimed at improving surveillance of approved drugs and reducing adverse drug reactions. Pharmacogenomics research is increasingly directed at developing genomic diagnostics and tests with predictive ability for adverse drug reactions. This paper focuses on the problem of adverse drug reactions and reviews the evidence and the state of the science for the application of pharmacogenomics to adverse drug reactions.